Previsão do preço do milho para o Estado do Ceará - Almeida, José Wandemberg Rodrigues (2018)
The State of Ceará has a prominent role in the consumption and production of maize, which is subject to the country's economic performance and climatic conditions. The objective of this study is to forecast the average monthly price of maize (received by the producer) from a time series that covers the period from January 2005 to December 2017 to forecast the behavior of the Product Price Series agricultural corn, assisting corn grain producers in the state of Ceará in planning their sales. Data were collected monthly and purchased from the Brazilian Institute of Geography and Statistics (IBGE), Ceará. In order to carry out the forecast, the methodology used was Box-Jenkins, the autoregressive method integrated with moving average (ARIMA) is identified for such forecast. For the highlighted culture, the methodology captured several significant models, but through the criteria, AIC, SBC and Medium Square Error, it was possible to choose the best model, being ARIMA (2.1). In this way, the behavior of the price of the product is extremely cause for discussion and concern for the producers and financial institutions, since an unexpected decrease in its magnitude may compromise the ability to pay the financing.